The Oxygen Consumption and Metabolic Cost of Walking and Running in Adults With Achondroplasia - Sims, David T.; Onambélé-Pearson, Gladys L.; Burden, Adrian; Payton, Carl; Morse, Christopher I. (Frontiers in Physiology, 2018)
The disproportionate body mass and leg length of Achondroplasic individuals may affect their net oxygen consumption (VO2) and metabolic cost (C) when walking at running compared to those of average stature (controls). The aim of this study was to measure submaximal VO2 and C during a range of set walking speeds (SWS; 0.56 - 1.94 m•s-1, increment 0.28 m•s-1), set running speeds (SRS; 1.67 - 3.33 m•s-1, increment 0.28 m•s-1) and a self-selected walking speed (SSW). VO2 and C was scaled to total body mass (TBM) and fat free mass (FFM) while gait speed was scaled to leg length using Froude’s number (Fr). Achondroplasic The oxygen consumption and metabolic cost of walking and running in adults with Achondroplasia VO2TBM and VO2FFM were on average 29 and 35% greater during SWS (P < 0.05) and 12 and 18% higher during SRS (P < 0.05) than controls, respectively. Achondroplasic CTBM and CFFM were 29 and 33% greater during SWS (P < 0.05) and 12 and 18% greater during SRS (P < 0.05) than controls, respectively. There was no difference in SSW VO2TBM or VO2FFM between groups (P > 0.05), but at SSW CTBM and CFFM were 23 and 29% lower (P < 0.05) in the Achondroplasic group compared to controls, respectively. VO2TBM and VO2FFM correlated with Fr for both groups (r = 0.984 - 0.999, P < 0.05). Leg length accounted for the majority of the higher VO2TBM and VO2FFM in the Achondroplasic group, but further work is required to explain the lower Achondroplasic CTBM and CFFM at all speeds compared to controls.